Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am suppose to use the definition of a derivative to find $f'(2)$, where $f(x)= x^3 - 2x$

What do I do? I am not sure what they are asking, I can use the power rule and such but I know that is not what I am suppose to do.

share|cite|improve this question
Do you know $f'(x)$ for any $x$ ? Then take $x=2$. If you don't, read the answer of Peter Tamarnoff. – Student May 5 '12 at 0:52
up vote 3 down vote accepted

We have $f(x) = x^3-2x$.

We build the quotient:

$$\frac{{f(x + h) - f\left( x \right)}}{h} = \frac{{{{\left( {x + h} \right)}^3} - 2\left( {x + h} \right) - \left( {{x^3} - 2x} \right)}}{h}$$

We have to expand the expression in the denominator. We get

$$\frac{{f(x + h) - f\left( x \right)}}{h} = \frac{{{x^3} + 3h{x^2} + 3{h^2}x + {h^3} - 2x - 2h - {x^3} + 2x}}{h}$$

We now cancel terms:

$$\frac{{f(x + h) - f\left( x \right)}}{h} = \frac{{3h{x^2} + 3{h^2}x + {h^3} - 2h}}{h}$$

Now, we distribute (divide) the $h$ in the denominator to all terms

$$\frac{{f(x + h) - f\left( x \right)}}{h} = \frac{{3h{x^2} + 3{h^2}x + {h^3} - 2h}}{h} = 3{x^2} + 3hx + h - 2$$

Now we can take the limit with no trouble:

$$\mathop {\lim }\limits_{h \to 0} \frac{{f(x + h) - f\left( x \right)}}{h} = \mathop {\lim }\limits_{h \to 0} 3{x^2} + 3hx + h - 2 = 3{x^2} - 2$$

So $f'(x) = 3x^2-2$. So $f'(2) = 3\cdot 2^2-2 = 10$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.